High resolution refractive index and temperature sensor with Fano resonance in disk and parenthesis-shaped plasmonic cavities - Shiva Khani; Mohsen Hayati (Results in Optics)
A surface plasmon-based sensor with high resolution for refractive index and temperature sensing is proposed in this work. This structure comprises a disk cavity (DC) coupled to four parenthesis-shaped cavities (PSCs) and two plasmonic waveguides. The finite difference time domain (FDTD) numerical method is utilized to study the suggested sensor’s performance. The frequency response of the suggested sensor has a Fano resonance (FR) mode with a sharp edge at the wavelength range of 700–800 nm which is suitable for sensing applications. The generated FR mode is tunable, and its location is tuned by varying the radii of DC and PSCs. Results show that the maximum sensitivity (Sλ) of 735 nm/RIU is obtained, and the FoM* value of 25,357 RIU−1 is also realized for the suggested plasmonic sensor. As an application for the sensor topology, it is simulated again using the FDTD method for different ambient temperatures. The suggested sensor achieves a relatively high-temperature Sλ of about 0.285 nm/oC. Due to the noteworthy and simple structure of the suggested sensor and its high FoM*, it may be an appropriate candidate for optical integrated circuits, especially in high-sensitive sensors.